Professional Ethical Aspects in the Study and Internship Environment: Research in Tallinn Health Care College - Kont, Kate-Riin; Rannula, Kateriina; Puura, Kristiina (Acta Paedagogica Vilnensia, 2021)
The exposure of healthcare professionals to (un)ethical situations starts in the educational institution, and the first serious cases occur during internships. The aim of the current study is to investigate the problems and causes (concerning unethical situations) related to students’ perception of ethics in the study and practice environment and to describe the awareness of Tallinn Health Care College’s students of professional ethics and the use of existing support systems in solving unethical problems.The findings indicated the importance of ethical communication and behaviour by all respondents. Empathy, ethical feedback, and confidentiality were perceived to be an integral part of ethical standards within the study and training environment. Respondents pointed out that ethical issues may occur not only between a health care professional and a patient, but also between a health care professional and doctor, supervisor, or teacher. A practical approach to ethical decision-making integrated into professional training has been assessed by all respondents.
Keywords: health care education; students; ethics; study environment; internship environment; support system; qualitative study